Ataxia telangiectasia: learning from previous mistakes. (14th December 2012) - Kumar, Naveen; Aggarwal, Puneet; Dev, Nishanth; kumar, Gunjan
Abstract : Ataxia telangiectasia is an early onset neurodegenerative disorder. We report a case of childhood onset ataxia and ocular telangiectasia, presenting with pulmonary infection. The patient was diagnosed as ataxia telangiectasia. The patient succumbed to death owing to late diagnosis and sepsis.